Observações da quantidade total de ozono e da radiação de UV nos Açores - Henriques, Diamantino; Carvalho, Fernanda; Fialho, Paulo (2005)
Comunicação apresentada no 4º Simpósio de Meteorologia e Geofísica da APMG – 6º Encontro Luso-Espanhol de Meteorologia, Sesimbra, 14-17 Fevereiro de 2005. First results of total ozone and ultraviolet radiation measurements carried out with a Brewer Spectrophotometer MKII in Terceira Is. (Azores) are presented. A brief description of the Brewer Spectrophotometerand and total ozone and sulphur dioxide retrieval method is done. Six months of Brewer and TOMS total ozone data are compared and analysed as well as UV changes during a selected period. These measurements are a part of the Portuguese Meteorological contribution for the development of a Global Station in the scope of the GAW/WMO programme in close cooperation with Azores University. The installation and operation of this instrument are partially funded by ROCA II (FCT) and CIMAAT (INTERREG IIIB – Project CLIMAAT – MAC 2.3/A3) projects. Ground based measurements collected at Terceira Is. should be useful on long term referencing and assessing of the performance of space-borne instruments over North Atlantic Region.